2004
DOI: 10.1191/0961203304lu1081oa
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor (EGFR) gene Bsr I polymorphism is associated with systemic lupus erythematosus

Abstract: The purpose of this study was to determine if epidermal growth factor receptor (EGFR) gene polymorphism was a marker of susceptibility to or severity of Chinese patients with systemic lupus erythematosus (SLE) in Taiwan. The study included 119 Chinese patients with SLE. One hundred unrelated healthy individuals living in central Taiwan served as control subjects. Polymorphisms of the EGFR Bsr I gene were typed from genomic DNA. The genotypes, allelic frequencies and carriage rates were compared between SLE pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…On the other hand, our analyses of allelic, genotypic and halplotype frequencies suggest that the T allele has a protective effect at rs17337023. Although the study of rs11543848 SNP showed no such risk association (Table 1), the risk association of the rs17337023 SNP in autoimmune diseases was further supported by previous study of our group in identifying the association of rs17337023 SNP with SLE [13]. However, we found that the EGFR polymorphisms have no association with clinical features of RA, which is similar to our previous findings in SLE [13].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, our analyses of allelic, genotypic and halplotype frequencies suggest that the T allele has a protective effect at rs17337023. Although the study of rs11543848 SNP showed no such risk association (Table 1), the risk association of the rs17337023 SNP in autoimmune diseases was further supported by previous study of our group in identifying the association of rs17337023 SNP with SLE [13]. However, we found that the EGFR polymorphisms have no association with clinical features of RA, which is similar to our previous findings in SLE [13].…”
Section: Discussionsupporting
confidence: 89%
“…Although the study of rs11543848 SNP showed no such risk association (Table 1), the risk association of the rs17337023 SNP in autoimmune diseases was further supported by previous study of our group in identifying the association of rs17337023 SNP with SLE [13]. However, we found that the EGFR polymorphisms have no association with clinical features of RA, which is similar to our previous findings in SLE [13]. Although the exact pathogenic mechanism relating these polymorphisms to these chronic inflammatory diseases still remain unknown, the extremely complex signaling network should be considered in the disease progression.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…EGFR has been found to be the predominantly expressed receptor in synovial fibroblasts (78). It has been shown that the EGFR 2133A/T polymorphism (rs17337023) was associated with malignant oral keratinocytes (Shintani et al ., ), SLE (Huang et al ., ), endometriosis and leiomyomas (Hsieh et al ., ). To the best of our knowledge, there is only one report regarding the association between EGFR polymorphisms and RA (Lo et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, some autoimmune diseases associated with bridge proteins are found to be related to BLADs. Specifically, EGFR which interacts with SH2B3 associated with APS ( Supplementary Figure 2 ), is related to systemic lupus erythematosus (SLE) (88). Surprisingly, an increasing number of studies (8991) have found APS in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%